The Fluorescent Palette of DNA-Templated Silver Nanoclusters for Biological Applications - Yang, Min; Chen, Xu; Su, Yuan; Liu, Haiyan; Zhang, Hongxing; Li, Xiangyang; Xu, Wentao (Frontiers in Chemistry, 2020)
Recently years have witnessed a surge in application of DNA-AgNCs in optics, catalysis, sensing, and biomedicine. DNA-templated silver nanoclusters (DNA-AgNCs), as emerging fluorophores, display superior optical performance since their size is close to the Fermi wavelength. DNA-AgNCs possess unique features, including high fluorescence quantum yields and stability, biocompatibility, facile synthesis, and low toxicity, which are requisite for fluorescent probes. The fluorescent emission of DNA-AgNCs can cover the violet to near-infrared (NIR) region by varying the DNA sequences, lengths, and structures or by modifying the environmental factors (such as buffer, pH, metal ions, macromolecular polymers, and small molecules). In view of the above excellent properties, we overview the DNA-AgNCs from the viewpoints of synthesis and fluorescence properties, and summarized its biological applications of fluorescence sensing and imaging.